(untitled) (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2018)
Gender issues have received much attention, in fact gender equality in fishing communities is still experiencing obstacles. The factors that play a role in positioning women as side actors in fishery activities and dominant actors in fisheries are men. This study aims to analyze the characteristics of fishermen households in Pulau Kelapa. In addition, this study aims to find out how the level of gender equality that exist in fishermen households in Pulau Kelapa. The results of this study indicate the majority of residents are at the age of the end of adult education level of women on average smp and men sd, the number of household dependent 4-5 people and income income is very low. In addition, gender inequalities occur because access control benefits and dominant resources are performed by men. Keywords: domestic fishermen, gender analysis, gender equality ———————Â ABSTRAK Isu gender telah banyak mendapat perhatian, kenyataannya kesetaraan gender dalam masyarakat nelayan masih mengalami hambatan. faktor yang berperan dalam memposisikan perempuan sebagai pelaku sampingan dalam kegiatan perikanan dan pelaku dominan dalam perikanan adalah laki-laki. Penelitian ini bertujuan untuk menganalisis karakteristik rumah tangga nelayan di Pulau Kelapa. Selain itu, penelitian ini bertujuan untuk mengetahui bagaimana tingkat kesetaraan gender yang ada di rumah tangga nelayan di Pulau Kelapa. Hasil dari penelitian ini menunjukkan mayoritas warga berada pada umur dewasa akhir tingkat pendidikan perempuan rata-rata smp dan laki-laki sd, Jumlah tanggungan rumah tangga 4-5 orang serta pendapatan pendapatan yang sangat rendah. Selain itu, terjadi ketimpangan gender Karena akses kontrol manfaat dan sumber daya dominan dilakukan oleh laki -laki. Kata kunci: analisis gender, kesetaraan gender, rumah tangga nelayanÂ